Using masking metrics as a means to quantify effect and guide mitigation measures of underwater anthropogenic noise - R. E. Burnham; S. Vagle (Ecosphere)
Abstract Anthropogenic noise in oceanic soundscapes is increasing, as is concern for its impacts on marine life. Until now, the potential effects have been considered by the comparison of sound levels to defined thresholds. Here, the influence of acoustic masking on a species is considered, quantifying the proportional reduction in range for acoustic signals as one means to characterize the impact of acoustic disturbance. The use of this metric is demonstrated by calculating the potential for masking communication calls and echolocation signals of southern resident killer whales (Orcinus orca) in the Salish Sea, British Columbia, subjected to significant commercial vessel traffic noise. The use of thresholds facilitates an empirical interpretation of changes in the sound field over space and time, whereas a masking metric determines when and where a whale's ability to send and receive acoustic information will be most obstructed. By considering the level of masking, the severity of a response might be distinguished. For example, a 0%–24% range reduction may be overcome by adaptive signaling, but this may not be possible when communication or echolocation range is reduced by 75% or more. This degree of masking was found in known foraging areas for southern residents, suggesting consequences to their success in finding and capturing food. Masking metrics will be useful to managers and policy makers to better understand acoustic disturbance of marine species and determine individual‐ to population‐level consequences of anthropogenic noise additions to soundscapes.